2015
DOI: 10.1177/003335491513000510
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Differences among Three New Indicators of HIV Infection Progression

Abstract: Objective. This study proposes three indicators of, and assesses the disparities and trends in, the risk of HIV infection progression among people living with diagnosed HIV infection in the United States.Methods. Using data reported to national HIV surveillance through June 2012, we calculated the AIDS diagnosis hazard, HIV (including AIDS) death hazard, and AIDS death hazard for people living with diagnosed HIV infection for each calendar year from 1997 to 2010. We also calculated a stratified hazard in 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…People with HIV (PWH) whose mode of HIV acquisition was intravenous drug use are at higher risk of progression to AIDS, death due to AIDS, and all-cause mortality even when controlling for access to care and antiretroviral therapy (ART) duration. [1][2][3][4] Although high-risk lifestyle or death from comorbid conditions, such as bacterial infection or hepatitis C, certainly contribute, chronic immune activation may play an important role. In an observational study of people with a history of injecting drugs, an inflammatory index constructed from serum interleukin (IL)-6 and soluble tumor necrosis factor-a-receptor I (sTNF-a-RI) was associated with frailty and increased mortality in PWH and people without HIV who inject drugs.…”
Section: Introductionmentioning
confidence: 99%
“…People with HIV (PWH) whose mode of HIV acquisition was intravenous drug use are at higher risk of progression to AIDS, death due to AIDS, and all-cause mortality even when controlling for access to care and antiretroviral therapy (ART) duration. [1][2][3][4] Although high-risk lifestyle or death from comorbid conditions, such as bacterial infection or hepatitis C, certainly contribute, chronic immune activation may play an important role. In an observational study of people with a history of injecting drugs, an inflammatory index constructed from serum interleukin (IL)-6 and soluble tumor necrosis factor-a-receptor I (sTNF-a-RI) was associated with frailty and increased mortality in PWH and people without HIV who inject drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, HIV testing motivated by symptoms would cause a late diagnosis for HIV-infected individuals. Further results of previous studies also showed that those diagnosed at medical institutions were at higher risk of late-stage diagnosis of HIV compared with other sample sources [38]. Moreover, it is possible that the HIV-infected individuals who participated in the unique survey received early access to diagnosis, treatment and support, and HIV care.…”
Section: Discussionmentioning
confidence: 90%